You need to write the following formula such that:
`a_7 = a_6*q`
`a_6 = a_5*q`
`a_5 = a_4*q`
Replace `a_4*q ` for `a_5` , such that:
`a_6 = a_4*q*q => a_6 = a_4*q^2`
Replace `a_4*q^2` for `a_6` such that:
`a_7 = a_4*q^2*q => a_7 = a_4*q^3 => q^3 = (a_7)/(a_4) => q = root(3)((a_7)/(a_4))`
`q = root(3)((2/3)/(-18)) => q = root(3)(-1/27) => q = root(3)(-1/(3^3))`
`q = -1/3`
You may find `a_6` such that:
`a_6 = (a_7)/q => a_6 = (2/3)/(-1/3) => a_6 = -2`
Hence, evaluating `a_6 ` yields `a_6 = -2.`
No comments:
Post a Comment